Endothelial CD74 mediates macrophage migration inhibitory factor protection in hyperoxic lung injury. Issue 5 (21st January 2015) - Sauler, Maor; Zhang, Yi; Min, Jin‐Na; Leng, Lin; Shan, Peiying; Roberts, Scott; Jorgensen, William L.; Bucala, Richard; Lee, Patty J.
ABSTRACT: Exposure to hyperoxia results in acute lung injury. A pathogenic consequence of hyperoxia is endothelial injury. Macrophage migration inhibitory factor (MIF) has a cytoprotective effect on lung endothelial cells; however, the mechanism is uncertain. We postulate that the MIF receptor CD74 mediates this protective effect. Using adult wild‐type (WT), MIF‐deficient ( Mif ‐/‐ ), CD74‐deficient ( Cd74 ‐/‐ ) mice and MIF receptor inhibitor treated mice, we report that MIF deficiency or inhibition of MIF receptor binding results in increased sensitivity to hyperoxia. Mif ‐/‐ and Cd74 ‐/‐ mice demonstrated decreased median survival following hyperoxia compared to WT mice. Mif ‐/‐ mice demonstrated an increase in bronchoalveolar protein (48%) and lactate dehydrogenase (LDH) (68%) following 72 hours of hyperoxia. Similarly, treatment with MIF receptor antagonist resulted in a 59% and 91% increase in bronchoalveolar lavage protein and LDH, respectively. Inhibition of CD74 in primary murine lung endothelial cells (MLECs) abrogated the protective effect of MIF, including decreased hyperoxia‐mediated AKT phosphorylation and a 20% reduction in the anti‐apoptotic effect of exogenous MIF. Treatment with MIF decreased hyperoxia‐mediated H2AX phosphorylation in a CD74‐dependent manner. These data suggest that therapeutic manipulation of the MIF‐CD74 axis in lung endothelial cells may be a novel approach to protect against acute oxidative stress.—Sauler, M., Zhang, Y., Min, J.‐N., Leng, L., Shan, P., Roberts, S., Jorgensen, W. L., Bucala, R., Lee, P. J. Endothelial CD74 mediates macrophage migration inhibitory factor protection in hyperoxic lung injury. FASEB J. 29, 1940‐1949 (2015). www.fasebj.org